HEALTH STATUS OF FEMALE TEENAGERS, SUFFERING FROM CONSTITUTIVE AND EXOGENOUS OBESITY - S.Ya. Volgina; M.K. Valiullina ("Paediatrician" Publishers LLC, 2006)
The article deals with the research findings of the health status of 120 female teenagers, suffering from constitutive and exogenous obesity and 116 girls of the same age and standard weight. The authors gave complete characteristics for the somatic, psychic and psychological elements of the teenager's health. They have assessed the consumatory behaviour of the girls. It has been revealed that among all the examined patients with hyperphagia 6,7% are suffering from nervous bulimia. the researchers stress the importance of the comprehensive examination of the female teenagers, suffering from obesity, that effects the quality improvement of the medical treatment they receive. Key words: constitutive and exogenous obesity, female teenagers, health status.